Intensive voluntary wheel running may restore circadian activity rhythms and improves the impaired cognitive performance of arrhythmic Djungarian hamsters. (20th October 2016) - Weinert, Dietmar; Schöttner, Konrad; Müller, Lisa; Wienke, Andreas
ABSTRACT: Circadian rhythms are highly important not only for the synchronization of animals and humans with their periodic environment but also for their fitness. Accordingly, the disruption of the circadian system may have adverse consequences. A certain number of animals in our breeding stock of Djungarian hamsters are episodically active throughout the day. Also body temperature and melatonin lack 24-h rhythms. Obviously in these animals, the suprachiasmatic nuclei (SCN) as the central pacemaker do not generate a circadian signal. Moreover, these so-called arrhythmic (AR) hamsters have cognitive deficits. Since motor activity is believed to stabilize circadian rhythms, we investigated the effect of voluntary wheel running. Hamsters were bred and kept under standardized housing conditions with food and water ad libitum and a 14 L/10 D lighting regimen. AR animals were selected according to their activity pattern obtained by means of passive infrared motion detectors. In a first step, the daily activity behavior was investigated for 3 weeks each without and with running wheels. To estimate putative photic masking effects, hamsters were exposed to light (LPs) and DPs and also released into constant darkness for a minimum of 3 weeks. A novel object recognition (NOR) test was performed to evaluate cognitive abilities both before and after 3 weeks of wheel availability. The activity patterns of hamsters with low wheel activity were still AR. With more intense running, daily patterns with higher values in the dark time were obtained. Obviously, this was due to masking as LPs did suppress and DPs induced motor activity. When transferred to constant darkness, in some animals the daily rhythm disappeared. In other hamsters, namely those which used the wheels most actively, the rhythm was preserved and free-ran, what can be taken as indication of a reconstitution of circadian rhythmicity. Also, animals showing a 24-h activity pattern after 3 weeks of extensive wheel running were able to recognize the novel object in the NOR test but not so before. The results show that voluntary exercise may reestablish circadian rhythmicity and improve cognitive performance.